Classification Systems, Social Hierarchies, and Gender: Examining Indian "Light-Classical" Music - Ollikkala, Robert (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
Classification systems are connected to a socio-cultural and musical canon. In her introduction to Musicology and Difference (1993), Ruth Solie made the point that classification systems in music involve, imply, and reinforce social hierarchies. What Solie had to say about the Western classification system applies equally well to India. This study supports the assumption, which I believe will hold true for other geographic regions, that there are universal implications to the term "classical," implications that include, but reach far beyond, the musical. Specific to the Indian situation, however, are the particular historic dynamics involved in the subsidiary category known as "light-classical" music.